Age effects and heuristics in decision making - Tibor Besedes; Carey Deck; Sudipta Sarangi; Mikhael Shor (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Using controlled experiments, we examine how individuals make choices when faced with multiple options. Choice tasks are designed to mimic the selection of health insurance, prescription drug, or retirement savings plans. In our experiment, available options can be objectively ranked allowing us to examine optimal decision making. First, the probability of a person selecting the optimal option declines as the number of options increases, with the decline being more pronounced for older subjects. Second, heuristics differ by age with older subjects relying more on suboptimal decision rules. In a heuristics validation experiment, older subjects make worse decisions than younger subjects.
Keywords: C91; D03; I18; 330; Experiments; decision making; optimal choice; age effects; heuristics; Entscheidung; Test; Altersgruppe